Measuring the thermal conductivity of the GaN buffer layer in AlGaN/GaN HEMTs. Issue 8 (23rd February 2015) - Power, Máire; Pomeroy, James W.; Otoki, Yohei; Tanaka, Takeshi; Wada, Jiro; Kuzuhara, Masaaki; Jantz, Wolfgang; Souzis, Andrew; Kuball, Martin
<x xml:space="preserve">Abstract</x> The thermal conductivity of the GaN buffer layer in AlGaN/GaN devices can be determined by measuring the vertical temperature gradient through this layer. In this work, diamond micro‐thermometers and standard micro‐Raman thermography were used to determine the surface and volumetric depth average temperature, respectively, of the carbon‐doped GaN buffer layer in AlGaN/GaN transistors. By comparing measured temperatures with finite element thermal simulation, a thermal conductivity of 200 ± 20 Wm−1 K−1 was obtained for a carbon‐doped GaN layer with a doping concentration of 1017 cm−3.